2017
DOI: 10.1186/s12913-017-2214-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of the STRATIFY and Downton instruments for evaluating the risk of falls by hospitalised acute-care patients: a multicentre longitudinal study

Abstract: BackgroundFalls are major adverse events in hospitals. The appropriateness of using risk assessment instruments for falls in hospitals has recently been questioned, although the research performed in this respect presents some methodological shortcomings. The purpose of the present study is to evaluate the accuracy of the Downton and STRATIFY instruments to determine the risk of falls and to predict their incidence in acute care hospitals in the public health system in Andalusia (Spain).MethodsA longitudinal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…24 The sensitivity and specificity of the fall risk assessment tool were lower than those previously reported for the STRATIFY. 25 They were also lower than the results reported in a systematic review by Matarese et al 13 The positive and negative predictive values were similar to those reported in a study 17 where an MFS cutoff score of 50 was used for neurological patients. The sensitivity, specificity, and predictability of the tool were low overall, which suggests the need to develop a tool reflecting the characteristics of the clinical setting to accurately predict falls.…”
Section: Discussionsupporting
confidence: 64%
“…24 The sensitivity and specificity of the fall risk assessment tool were lower than those previously reported for the STRATIFY. 25 They were also lower than the results reported in a systematic review by Matarese et al 13 The positive and negative predictive values were similar to those reported in a study 17 where an MFS cutoff score of 50 was used for neurological patients. The sensitivity, specificity, and predictability of the tool were low overall, which suggests the need to develop a tool reflecting the characteristics of the clinical setting to accurately predict falls.…”
Section: Discussionsupporting
confidence: 64%
“…Among the models that have been tested in different clinical groups (Aranda‐Gallardo, Luna‐Rodrigues, Vazquez‐Blanco, Canca‐Sanchez, & Morales‐Asencio, ; Poe et al., ) there has been substantial variability in sensitivity and specificity values: the Morse Fall Scale (sensitivity 78%, specificity 83%) (Morse et al., ); the STRATIFY tool (score ≥2 sensitivity 92%, specificity 68% and score ≥3 sensitivity 54%, specificity 88%) (Oliver et al., ); the Hendrich II Fall Risk Model (sensitivity 74%, specificity 73%) (Hendrich et al., ) and the Johns Hopkins Fall Risk Assessment Tool (sensitivity 69%, specificity 60%) (Poe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The compilation of the scale is not performed through direct observation of the patient, but the evaluator reports the score based on information obtained from the previous observation or from other caregivers. STRATIFY has been extensively studied in intensive care units in Australia, Europe and Canada [ 48 ] and has also been applied in numerous geriatric and rehabilitation departments [ 49 ]. In these contexts, it has long been considered the “Gold standard” tool to be used at patient admission thanks to the high sensitivity value demonstrated by numerous studies (between 73.7% and 93.0%) and the simplicity and speed of application (3 min).…”
Section: Discussionmentioning
confidence: 99%